Curriculum learning organization (study at Madrasah Ibtidaiyah) - Zulia Nurul Faizah; Oktaviani Adhi Suciptaningsih; Siti Faizah (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The role of the curriculum for educational units is absolute. Therefore, curriculum development must be adjusted to the madrasah environment's identity and potential, including in organizing learning. The organization of learning is closely related to the learning process. This can also be one of the community's attractions to the madrasah. This study aims to examine the components of organizing intracurricular, co-curricular, and extracurricular learning at MI Miftahul Ulum Bukur. Researchers used interviews and documentation. The research findings state that intracurricular learning on national content is arranged and carried out according to the guidelines of the Ministry of Education, Culture, Research and Technology and the Decree of the Minister of Religion but also maintains the potential of teachers such as maintaining science and social studies subjects that apply in each semester for all levels of grades III-VI. The local content that is applied shows the madrasah's identity, such as Mabadi, 'Alala, and BTQ. Co-curricular learning is carried out through P5RA activities, and the selection of activities is based on the needs and availability of surrounding resources. Extracurricular learning as an effort of madrasah to achieve in non-academic fields offers scouting activities, drumband, qira'at, banjari, speech (English and Indonesian), calligraphy, and English. This research can be used as a reference for other madrasahs to observe, imitate, and modify the organization according to their educational units. AbstrakPeran kurikulum bagi satuan pendidikan adalah hal yang mutlak. Oleh karenanya, pengembangan kurikulum harus disesuaikan dengan identitas dan potensi lingkungan madrasah termasuk dalam mengorganisasikan pembelajaran. Pengorganisasian pembelajaran memiliki keterkaitan yang erat dengan proses pembelajaran. Pula hal ini bisa menjadi salah satu daya tarik masyarakat terhadap madrasah. Penelitian ini bertujuan mengkaji komponen pengorganisasian pembelajaran intrakurikuler, kokurikuler, dan ekstrakurikuler MI Miftahul Ulum Bukur. Peneliti menggunakan wawancara dan dokumentasi. Temuan penelitian menyatakan bahwa pembelajaran intrakurikuler pada muatan nasional disusun dan dilakukan sesuai pedoman Kemdikbudristek dan Keputusan Menteri Agama namun juga tetap mempertahankan potensi guru seperti mempertahankan mata pelajaran IPA dan IPS berlaku di tiap semester untuk semua jenjang kelas III-VI. Sedangkan muatan lokal yang terapkan benar-benar menunjukkan identitas madrasah seperti Mabadi, ‘Alala, dan BTQ. Pembelajaran kokurikuler dilaksanakan melalui kegiatan P5RA dan pemilihan kegiatannya berdasarkan kebutuhan dan ketersediaan sumber daya sekitar. Pembelajaran ekstrakurikuler sebagai upaya madrasah untuk berprestasi dibidang non akademik menawarkan kegiatan pramuka, drumband, qira’at, banjari, pidato (bahasa Inggris dan bahasa Indonesia), kaligrafi, serta bahasa Inggris. Penelitian ini bisa dijadikan referensi bagi madrasah lain untuk mengamati, meniru, dan memodifikasi pengorganisasian tersebut sesuai satuan pendidikannya.Kata Kunci: ekstrakurikuler; intrakurikuler; kokurikuler; kurikulum